5(y+2)+3(y-4)=0

Simple and best practice solution for 5(y+2)+3(y-4)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5(y+2)+3(y-4)=0 equation:


Simplifying
5(y + 2) + 3(y + -4) = 0

Reorder the terms:
5(2 + y) + 3(y + -4) = 0
(2 * 5 + y * 5) + 3(y + -4) = 0
(10 + 5y) + 3(y + -4) = 0

Reorder the terms:
10 + 5y + 3(-4 + y) = 0
10 + 5y + (-4 * 3 + y * 3) = 0
10 + 5y + (-12 + 3y) = 0

Reorder the terms:
10 + -12 + 5y + 3y = 0

Combine like terms: 10 + -12 = -2
-2 + 5y + 3y = 0

Combine like terms: 5y + 3y = 8y
-2 + 8y = 0

Solving
-2 + 8y = 0

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 8y = 0 + 2

Combine like terms: -2 + 2 = 0
0 + 8y = 0 + 2
8y = 0 + 2

Combine like terms: 0 + 2 = 2
8y = 2

Divide each side by '8'.
y = 0.25

Simplifying
y = 0.25

See similar equations:

| 20-2y=4+0.5y | | 3x^2+30x+12=0 | | 7*h=-51 | | (5x)=(3x+13) | | -3.3(y+8)-2.5y= | | -9=9(h-2) | | 3x^2+30x-12=0 | | (3x-9)+(x+7)=90 | | -y+16+6y=44 | | z+10=z-5 | | 2y^2=-16y | | (2x+6)(3x+10)=0 | | -2x-8=4x+16 | | 3z^2-7z+4=0 | | 5(-1)-2= | | 176-6x=39x-21 | | 0.45(5-0.4n)=-3.2 | | 5x-2=-2x-9 | | 3-18+8x=67 | | 2(-3+4y)=-6 | | 6m/5=24 | | -8*x+3=251 | | 15y^2+46y+16=0 | | 17p-3=48 | | 4x+2=2x+24 | | x^4+3x^2-54=0 | | 4w^2=-28w | | =3ln(8) | | 7t-8=4t-2 | | 3x-8=10-3x | | 5n(2n+8)=0 | | -5x+4=-40+6x |

Equations solver categories